(untitled) (Eurasian Journal of Ecology, 2022)
The global pollution of environment urges the screening of effective natural protectors for the correc- tion of toxic and genotoxic action of xenobiotics. Medicinal herbs contain a complex of biologically ac- tive compounds that are the potential sources of such a protective agent. In current study the mutagenic and antimutagenic activity of alcoholic extracts of peppermint (Mentha piperita L.) and thyme (Thymus vulgaris L.), family Lamiaceae, was studied using the chromosome aberration assay (metaphase cytoge- netics) in barley. The ability of extracts to significantly reduces methyl methanesulfonate-induced mu- tagenesis under preliminary or subsequent tinctures exposure was established (p<0.05). The modifying effect of peppermint and thyme tinctures was also studied under the exposure to rocket fuel unsymmetri- cal dimethylhydrazine (UDMH, 1,1-dimethylhydrazine) which possess mutagenic and genotoxic activ- ity. Subsequent test-object treatment with tinctures and UDMH significantly decrease the frequency of induced aberrant cells and number of chromosomal aberrations (p<0.05). In case of both mutagens, the rate of mutagenesis inhibition depended both on the order of tinctures and mutagen treatment and extracts concentration. The efficacy of antimutagenic activity of Mentha piperita L. and Thymus vulgaris L. tinctures was assessed with reduction factor (RF) which in both experiments exceeded 40% testifying to inhibition of MMS and UDMH induced mutagenesis. Data obtained indicate the antimutagenic ac- tivity of extracts of peppermint (Mentha piperita L.) and thyme (Thymus vulgaris L.) conditioned on the presence of biologically active compounds of various nature. Key words: medicinal herbs, biologically active compounds, induced mutagenesis, antimutagenic activity, chromosomal aberrations.